Analisis Kebutuhan Pengembangan E-Modul Berbasisa Education For Sustainable Development (ESD) Materi Pengelolaan Sampah Melalui 3R di Sekolah Dasar - Amelia Ansori; Ghullam Hamdu; Agnestasia Ramadhani (STKIP Subang, 2025)
Education plays a crucial role in shaping a generation capable of addressing global challenges, including environmental issues such as waste management. This study aims to analyze the need for the development of an electronic module (e-module) based on Education for Sustainable Development (ESD) in elementary school science (IPAS) lessons, particularly in the topic of waste management using the 3R principles (Reduce, Reuse, Recycle). The ESD approach is considered essential to instill environmental sustainability awareness from an early age. This research employed a descriptive qualitative method conducted in two elementary schools in Tasikmalaya City: SDN Panglayungan and SDN Galunggung, involving fifth-grade teachers and students as subjects. Data collection techniques included document analysis of teaching materials and in-depth interviews with teachers to identify the availability, use, and need for ESD-based learning resources. The findings reveal that while digital learning facilities are adequately available, teachers’ understanding of the ESD approach and the availability of interactive e-modules remain limited. Therefore, the development of engaging, interactive, and contextual ESD-based e-modules is urgently needed to enhance learning quality and embed sustainability values in students.